Marketing for Hospitality and Tourism / Fourth Edition - Bowen John; Kotler Philip; Makens James (Pearson - Prentice Hall, 2006)
Understanding the Hospitality and Tourism Marketing Process, Introduction: Marketing for Hospitality and Tourism, Service Characteristics of Hospitality and Tourism Marketing, The Role of Marketing in Strategic Planning, Developing Hospitality and Tourism Marketing Opportunities and Strategies, The Marketing Environment, Marketing Information Systems and Marketing Research, Consumer Markets and Consumer Buying Behavior, Organizational Buyer Behavior of Group Market, Market Segmentation and Targeting and Positioning, Developing the Hospitality and Tourism Marketing Mix, Designing and Managing Products, Internet Marketing, Building Customer Loyalty Through Quality, Pricing Products: Pricing Considerations and Approaches and Strategy, Distributions Channels, Promoting Products: Communication and Promotion Policy and Advertising, Promoting Programs: Public Relations and Sales Promotion, Professional Sales, Managing Hospitality and Tourism Marketing, Electronic Marketing: Internet Marketing and Database Marketing and Direct Marketing, Destination Marketing, Next Year's Marketing Plan.